Humidity Control Ability of Porous Ceramics Prepared by Thermal Decomposition of Limestone and Dolomite - Parinya Somrang (Science Faculty of Chiang Mai University, 2020)
The use of low energy consumption materials for daily living has recently gained popularity in the selection process of household construction components. This study examined the properties of porous ceramics prepared by thermal decomposition of limestone and dolomite with respect to the humidity control by measuring their moisture absorption/desorption abilities. A spray dry technique was utilized to prepare the powder, while a simple pressing method was followed for fabrication of the samples. Porous ceramics that featured fine porosity were obtained after firing at a temperature range of 1100-1300°C. The porous samples exhibited the highest bending strength of 34.82 MPa, porosity 52.47%, specific surface area 2.97 m2/g and average pore size 0.41 μm. Within 5 hours, the porous samples showed the highest function of humidity control with moisture absorption at 18.14 g/m2 and desorption 49.05 g/m2. Microstructure observed by SEM presented that the functional porous ceramics consisted of fine interconnected pores. Moisture absorption/desorption abilities depend on porosity type and pore size distribution. These can be improved to create a pleasant environment and save energy consumption for living in tropical climate conditions.